Development Of A Flipped Classroom Learning System Based On Guided Inquiry On Electrolyte And Non-Electrolyte Solution Materials - Miftah Alfidyah; Mawardi Mawardi (Journal of Educational Sciences, 2022)
The era of education influenced by the industrial revolution 4.0 is called Education 4.0. Education 4.0 is an education that is characterized by the use of digital technology in the learning Therefore, research is needed that aims to develop a guided inquiry-based flipped classroom learning system using Moodle on electrolyte and non-electrolyte solutions, as well as to determine the level of validity and practicality of the products developed. This type of research is Educational Design Research (EDR) using the Plomp model. The subjects of this study were 3 chemistry lecturers at FMIPA UNP, 3 chemistry teachers, and 15 students in class XI IPA SMAN 8 Padang. This research was conducted to test the validity using the Aiken's V formula and the practicality test using the percentage formula. Five validators carried out the validity test and one-to-one evaluation by three students. The results of processing the validity test data are 0.88, indicating the valid category. For the data processing results, the practicality test for students is 88%, and the practicality test for teachers is 94% which shows the very practical category.